Execução provisória de astreintes no processo do trabalho - Chierighini, Luís Maurício (2014)
The purpose of this study is to systematize the debate over the provisional foreclosure of astreintes arising from breach of affirmative or negative obligation, or of an obligation to deliver specifically in labor proceedings. To that extent, the author analyzed the foreclosure proceeding as a tool to reach effectiveness in a legal dispute, finding in the instrument provided for in Article 461 and 461 -A of the Civil Procedure Code, implemented by the procedural reforms enacted by Law No. 8.952/1994 and No. 10.444/2002, a measure that meets this view of the proceeding as a tool to reach Justice . The author also addressed the subsidiary application of the aforementioned legal provisions in the labor proceedings, as well as the provisional foreclosure, generically considered, and, specifically, in labor proceedings. Subsequently, the author faced the specific subject of this study , namely, the provisional foreclosure of astreintes , approaching the vision of civil and labor procedure scholars, as well as current case law . Finally, after discussing the current trend of constitutionalization of labor law, the author analyzed the provisional foreclosure of astreintes in the labor proceedings from the perspective of a search for effectiveness of labor related foreclosure